The Impact of Performance Enhancement on Value of Care in Hospitals - Bertke, Peter; Nufer, Martin (Frontiers in Public Health, 2021)
Hospitals are facing big challenges: decreasing reimbursements are going alongside increasing costs and the necessity of investments. At the same time occuring, excellent quality of care and high patient satisfaction have to be assured. The dilemma of providing both with decreasing rather than increasing resources cannot be solved only by striving for economies of scales, by optimizing supply chain management or reduction of overhead. Possible effects of these measures most often are already exhausted and seldom have a positive impact on quality of care or patient satisfaction. Management is tempted to use its best known instruments to reduce costs, while medical staff’s focus is on quality of care and often battle against management as a perceived enemy. The solution to this dilemma lies in focusing on medical core processes that are directly linked to patients’ treatments and thereby improving all parameters of Michael Porter’s value equation: costs, outcome and patient satisfaction. This approach of performance enhancement presumes understanding, acceptance and constructive collaboration of two usually separated worlds: the medical-scientific world involved in patient care and the financial world of management. In this article, the authors explain performance enhancement for optimized delivery of care and how the dilemma mentioned above can be solved. The authors explain how performance enhancement can be achieved in daily clinical practice, which kind of obstacles have to be overcome, which changes are necessary within a hospital, how medical staff can be motivated and how the value of care equation can be influenced.